Policy on Children's Work and Labour. (18th December 2018) - Bourdillon, Michael; Carothers, Richard
Abstract : Current international child labour policies emphasise removing children from work rather than improving their well‐being. Prohibited 'child labour' extends beyond work shown to be harmful, and work in poorer, majority‐world societies is particularly targeted. These policies ignore benefits that children can gain from work, and have been developed largely without the involvement of the children, families and communities most concerned, limiting chances of successful outcomes. This paper argues for alternative approaches, developed in collaboration with children and their communities, focussing on children's well‐being and development, and protecting children from harm and exploitation while allowing them to benefit from appropriate work.